2009
DOI: 10.1002/eat.20655
|View full text |Cite
|
Sign up to set email alerts
|

Treating childhood obesity: Family background variables and the child's success in a weight‐control intervention

Abstract: Objective: To analyze whether caregiver and family characteristics predict success in a family-based lifestyle intervention program for children and adolescents.Method: Participants were 111 overweight and obese children (7-15 years) who attended a family-based weightreduction program. Body mass index (BMI) and BMI standard deviation scores (BMI-SDS) of index child, and BMI of family members, family adversity characteristics, depression, and attachment attitudes of the primary caregiver were assessed.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 35 publications
2
51
3
4
Order By: Relevance
“…When grouped according to familial predispositions, girls with familial obesity responded better to treatment than girls with no familial obesity, though girls without familial obesity reduced their degree of obesity as well. This finding was contrary to expectations since other studies have shown that familial obesity is associated with a poorer response to treatment [9][10][11][12]14]. However, familial predispositions to obesity related cardiovascular complications were in general not associated with the changes in BMI SDS in the obese children and adolescents enrolled in the multidisciplinary treatment protocol practised in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…When grouped according to familial predispositions, girls with familial obesity responded better to treatment than girls with no familial obesity, though girls without familial obesity reduced their degree of obesity as well. This finding was contrary to expectations since other studies have shown that familial obesity is associated with a poorer response to treatment [9][10][11][12]14]. However, familial predispositions to obesity related cardiovascular complications were in general not associated with the changes in BMI SDS in the obese children and adolescents enrolled in the multidisciplinary treatment protocol practised in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, the intervention approaches and the follow-up times during treatment varied from 12 [10,12,14] to 36 months [9] in-between these studies. Furthermore, many of the cited studies outline the effect of a familial predisposition to obesity [9][10][11][12][14][15][16][17][18] and only a few studies outline the effect of a familial predisposition to T2DM [12]. The studies concerning CVD only analyse the degree of obesity and not how these conditions influence childhood obesity treatment [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations